The regulation of genetically modified organisms : comparative approaches - Bodiguel, Luc.; Cardwell, Michael (Oxford : Oxford University Press, 2010)
The regulation of genetically modified organisms continues to generate controversy. On the one hand they are vital to ensuring food security, on the other hand, consumer resistance persists. This volume brings together scholars from across the globe to examine the regulation of GMOs from their own national and regional perspectives.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Genetically modified foods -- Law and legislation; Transgenic organisms -- Law and legislation